Claudia and mean Janine - Martin, Ann M., 1955-; Telgemeier, Raina; Martin, Ann M., 1955-; Lamb, Braden; Green, John Patrick, 1975- (New York, NY : Graphix, an imprint of Scholastic, 2016)
"Claudia and her sister, Janine, may as well be from two different planets. Claudia, who pays more attention to her artwork and The Baby-sitters Club than her homework, feels like she can't compete with her perfect sister. Janine studies nonstop, gets straight As, and even takes college-level courses! But when something unexpected happens to the most beloved person in their family, will the sisters be able to put aside their differences?"--Publisher.
"Based on the novel by Ann M. Martin"--Cover.
New March 2022.
Keywords: Babysitters Club (Imaginary organization) -- Comic books, strips, etc; Babysitters Club (Imaginary organization) -- Juvenile fiction; Girls -- Comic books, strips, etc; Girls -- Juvenile fiction; Babysitters -- Comic books, strips, etc; Babysitters -- Juvenile fiction; Clubs -- Comic books, strips, etc; Clubs -- Juvenile fiction; Sisters -- Comic books, strips, etc; Sisters -- Juvenile fiction; Grandmothers -- Comic books, strips, etc; Grandmothers -- Juvenile fiction; Graphic novels